L’insostenibile leggerezza del Metaverso: tra tensioni geopolitiche e questioni etico-politche - De Ruvo, Giuseppe (Filosofia Morale/Moral Philosophy, 2024)
This paper thematizes the critical issues underlying the emergence of the Metaverse, pointing out how it may exacerbate and radicalize geopolitical and ethical-political issues. In particular, we will examine how the emergence of the Metaverse might impact Sino-American relations and phenomena such as political radicalization, loss of decision-making autonomy and climate change. In conclusion, the article outlines a critical-philosophical attitude that should accompany the birth of the Metaverse